Effects of Pre‐Weaning Energy Substitutions on Post‐Weaning Follicle Development, Steroid Hormones and Subsequent Litter Size in Primiparous Sows. Issue 3 (26th October 2012) - Chen, TY; Stott, P; Bouwman, EG; Langendijk, P
Contents The present study investigated the effects of pre‐weaning energy substitutions on follicular development, endocrine characteristics and subsequent litter size in primiparous sows. Sows were fed a standard lactation diet (14.1 DE MJ/kg) and then allocated to a Control (C, n = 24), Fat (F, n = 23), Sugar (S, n = 23) or post‐weaning Regumate (positive control; R, n = 22) treatment at 9 days before weaning of the C, F and S treatments. During the treatment period (8 days), 1 kg of the lactation diet was substituted with 1 kg of a fat‐rich (F, 23.85 DE MJ/kg) or sugar‐rich (S, 15.75 DE MJ/kg) substitution for F and S sows, respectively. For the R treatment, sows were weaned 8 days earlier than other treatments and fed a lactation diet at 3.5 kg with two doses of altrenogest as topdressing from 1 day before weaning until the day on which the other sows were weaned. The F treatment aimed to increase energy intake, and the S treatment aimed to elevate post‐prandial glucose and insulin concentrations. Weaning‐to‐ovulation interval tended to be reduced in the S treatment compared with C (p = 0.06) and F (p = 0.08) treatments. Body weight (BW) loss during the treatment period, post‐weaning follicle development, plasma oestradiol and pre‐weaning leptin did not differ among C, F and S sows, although BW loss was lower and leptin was higher in the R treatment. Post‐ovulatory progesterone concentration in the S treatment was higher (p < 0.05). Sows in the S and R treatments had a greater proportion of litters with larger litter sizes (p < 0.05). The outcome suggests that increasing circulating insulin and glucose concentrations during late lactation or a week of metabolic recovery positively improves subsequent litter size in primiparous sows.